Tuning direct bandgap GeSn/Ge quantum dots' interband and intraband useful emission wavelength: Towards CMOS compatible infrared optical devices. (May 2018) - Baira, Mourad; Salem, Bassem; Madhar, Niyaz Ahamad; Ilahi, Bouraoui
Abstract: In this work, interband and intraband optical transitions from direct bandgap strained GeSn/Ge quantum dots are numerically tuned by evaluating the confined energies for heavy holes and electrons in Г-and L-valley. The practically exploitable emission wavelength ranges for efficient use in light emission and sensing should fulfill specific criteria imposing the electrons confined states in Г-valley to be sufficiently below those in L-valley. This study shows that GeSn quantum dots offer promising opportunity towards high efficient group IV based infrared optical devices operating in the mid-IR and far-IR wavelength regions. Graphical abstract: The practically exploitable interband and intraband emission wavelength from direct bandgap strained GeSn/Ge quantum dots are numerically tuned ensuring the fulfillment of specific criteria imposing the electrons confined states in Г-valley to be sufficiently below those in L-valley. This study suggests promising opportunity towards high efficient group IV QD based infrared optical devices operating in the mid-IR (2.2–4.3 μm) and far-IR (11.8–43 μm) wavelength regions.Image Highlights: Theoretical study of the practically exploitable wavelength range either issued from the interband and intraband optical transitions in GeSn quantum dots. Use of the most common GeSn/Ge quantum dots shape (dome and pyramid) with different Sn composition and sizes while ensuring the fulfillment of specific criteria imposing the electrons confined states in Г-valley to be sufficiently below those in L-valley. This study suggests promising opportunity towards high efficient group IV QD based infrared optical devices operating in the mid-IR (2.2–4.3 μm) and far-IR (11.8–43 μm) wavelength regions.